Nicole Oresme’s De moneta in the tradition of political treatises and reception of Politics in the 14th century - Giglio, Julián (Scripta Mediaevalia, 2023)
The present work investigates the way in which the postulates of the Aristotelian political ontology of the first book of Politics were received in two important political treatises of the first half of the 14th century, and how these can be traced as antecedents of the Oresmian treatise on money. Thereby, by analyzing the way in which John Quidort of Paris and Marsilius of Padua retake the Aristotelian text, which allows the reconstruction of an autonomous scientia civilis, some key concepts are determined that account for the emptying of the original logical-ontological content that they carry out, which is observed at the same time in the Oresmian treatise. Likewise, through the analysis of some specific passages in the works of these two authors, their implicit presence in the Oresmian treatise is analyzed, and how the latter is inserted into other latent discussions of the period.